1997
DOI: 10.1021/ef960229t
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Decarboxylation. A Reaction Sequence for the Study of Aromatic Structural Elements in Pocahontas No. 3 Coal

Abstract: Oxygen in basic solution has been used to oxidize Pocahontas No. 3 coal to a mixture of aromatic carboxylic acids, and copper(I) oxide in N-methylpyrrolidinone-quinoline has been used to decarboxylate the acids to provide a mixture of hydrocarbons. Most pendant alkyl groups have been removed in this sequence and the product distribution is much less complex than the product distributions that are obtained in direct oxidation reactions or in the analysis of coal liquids and extracts. Approximately 25% of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…3 coal was generated. This model was constructed based on a the review data of Stock and Muntean 1 , oxidation and decarboxylation data for aromatic clustersize frequency of Stock and Obeng 2 , and the combination of Laser Desorption Mass Spectrometry data with HRTEM 3 , enabled the inclusion of a molecular weight distribution. The model contains 21,931 atoms, with a molecular mass of 174,873 amu, and an average molecular weight of 714 amu, with 201 structural components.…”
Section: Disclaimermentioning
confidence: 99%
See 1 more Smart Citation
“…3 coal was generated. This model was constructed based on a the review data of Stock and Muntean 1 , oxidation and decarboxylation data for aromatic clustersize frequency of Stock and Obeng 2 , and the combination of Laser Desorption Mass Spectrometry data with HRTEM 3 , enabled the inclusion of a molecular weight distribution. The model contains 21,931 atoms, with a molecular mass of 174,873 amu, and an average molecular weight of 714 amu, with 201 structural components.…”
Section: Disclaimermentioning
confidence: 99%
“…3 was constructed in a similar manner to that already discussed 9 . Here the bulk data were obtained from the literature review of Stock and Muntean 1 , and the oxidation decarboxylation data to determined aromatic cluster-size relative abundance 2 , along with the molecular weight distribution determined from the combination of HRTEM and laser desorption mass spectrometry (LDMS) data. The details of the elucidation of the molecular weight distribution using the complimentary HRTEM and LDMS data are available elsewhere 3 .…”
Section: Experimental and Operational Datamentioning
confidence: 99%
“…A combination method of oxidation and decarboxylation is a feasible approach to convert brown coal to aromatic hydrocarbons with no use of hydrogen or hydrogen donors under mild conditions [3][4][5][6][7][8]. In the oxidation process, aromatic carboxylic acids are obtained from coal, and then during the decarboxylation process, carboxylic functional groups in aromatic carboxylic acids are removed to form aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…These authors identified numerous groups of phenyl-and naphthyl-PAC derivatives, including: phenylnaphthalenes, terphenyls, phenylphenanthrenes, phenyl-and diphenylbenzo [b]thiophenes, phenyldibenzothiophenes, phenylnaphtho[b]thiophenes, naphthylbenzo [b]thiophenes, phenyldibenzofurans, and tentatively identified phenyltriphenylenes, quater-, quinque-and sexiphenyls. Based on the knowledge about the natural occurrence of PhPACs and their formation processes during oxidative pyrolysis of coal and coal-derived materials (Marynowski et al, 2004;Meyer zu Reckendorf, 1997, 2000, as well as chemical decarboxylation and oxidation of hard coals (Stock and Obeng, 1997), it is believed that their origin is connected with freeradical OM phenylation reactions. Moreover, ionic versus free-radical phenylation experiments confirmed the formation of these compound groups according to the latter process (Rospondek et al, 2007(Rospondek et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%